Negotiation between Aesthetics and Social Issues in Reading Flaubert in Egypt: A Sensibility on Tour - Khanal, Niran (Mindscape: A Journal of English & Cultural Studies, 2025)
This paper explores an approach to read travel literature in order to balance between the pleasure of reading with aesthetic sensibility and social awareness for constructive criticism. The paper argues that excessive importance given to the social issues undermines the aesthetics of reading travel narratives. By the same token, overindulgence in aesthetics compromises with socially important agendas that need attention for the social well-being. Therefore, the challenge is how to balance between aestheticism and sociologism. To address these two extremes, the present study proposes an approach of negotiation between the two. For the purpose of examining how this approach works, I analyze Flaubert in Egypt: A Sensibility on Tour by Gustave Flaubert. The outcome of this study is that Flaubert’s expression of aesthetics that he experienced during his travel to Egypt is interwoven with the social fabrics of Egyptian societies of 19th century and his personal interaction with them. It uncovers the contesting relations between the narrator’s wishes and the social expectations. The significance of this study lies in its approach to make reading of travel narrative aesthetically pleasing and socially meaningful.